Energy budget and mechanisms of cold ion heating in asymmetric magnetic reconnection. Issue 9 (18th September 2017) - Toledo‐Redondo, Sergio; André, Mats; Khotyaintsev, Yuri V.; Lavraud, Benoit; Vaivads, Andris; Graham, Daniel B.; Li, Wenya; Perrone, Denise; Fuselier, Stephen; Gershman, Daniel J.; Aunai, Nicolas; Dargent, Jérémy; et al.
Abstract: Cold ions (few tens of eV) of ionospheric origin are commonly observed on the magnetospheric side of the Earth's dayside magnetopause. As a result, they can participate in magnetic reconnection, changing locally the reconnection rate and being accelerated and heated. We present four events where cold ion heating was observed by the Magnetospheric Multiscale mission, associated with the magnetospheric HallE field region of magnetic reconnection. For two of the events the cold ion density was small compared to the magnetosheath density, and the cold ions were heated roughly to the same temperature as magnetosheath ions inside the exhaust. On the other hand, for the other two events the cold ion density was comparable to the magnetosheath density and the cold ion heating observed was significantly smaller. Magnetic reconnection converts magnetic energy into particle energy, and ion heating is known to dominate the energy partition. We find that at least 10–25% of the energy spent by reconnection into ion heating went into magnetospheric cold ion heating. The total energy budget for cold ions may be even higher when properly accounting for the heavier species, namely helium and oxygen. LargeE field fluctuations are observed in this cold ion heating region, i.e., gradients and waves, that are likely the source of particle energization. Plain Language Summary: The magnetic field of Earth creates a natural shield that isolates and protects us from the particles and fields coming from our star, the Sun. This natural shield is called the magnetosphere and is filled by plasma. The particles coming from the Sun form another plasma called the solar wind and are usually deviated around the magnetosphere. However, under certain circumstances these two plasmas can reconnect (magnetic reconnection), and part of the energy and mass of the two plasmas is interchanged. Magnetic reconnection is the driver of storms and substorms inside the magnetosphere. In this work, we investigate what occurs to particles of very low energy (cold ions) of ionospheric origin when they reach the reconnecting boundary of the magnetosphere. It is found that they are energized and take an important part of the energy spent in reconnecting the plasmas. The plasma boundary develops spatial structures and emits waves that are able to heat the cold ions. Once heated, these cold ions irreversibly will escape the Earth's magnetosphere to never come back to Earth. Key Points: Observations of cold ion heating associated with magnetic reconnection Large electric field fluctuations (gradients and waves) in association with the cold ion heating At least 10 to 25% of the energy that goes into heating is used to heat cold ions